God Representations: An Exploratory Study on a Croatian Adolescent Sample - Užarević, Filip (Research in the social scientific study of religion, 2016)
The varieties of ways in which people think and feel about God, i.e. God representations (grs), are a relevant topic in psychology, yet under-researched in countries other than Western Europe and the United States. The aim of the current study was to investigate the dimensions of grs and their associations with religiosity in a sample of Eastern European (Croatian) adolescents. For the assessment of grs we created the God Representations Questionnaire (grq-21), and for measuring religiosity we used a multidimensional Religiosity questionnaire that distinguished between religious beliefs, ritual religiosity, and religious social behaviour. The sample consisted of 413 high school students attending Roman Catholic religion courses in Zagreb. Factor analysis of the grq-21 yielded four factors of grs: the traditional-positive, the abstract/distant, the playful, and the anthropomorphic. Regarding the relationship between dimensions of grs and religiosity, the traditional-positive dimension correlated positively with all religiosity dimensions, while the playful, abstract/distant, and anthropomorphic dimensions of grs correlated positively only with religious beliefs, but not ritual religiosity or social religious behaviour. The results are in accordance with previous findings from Western Europe and the United States, but also expand them.